A UV‐Responsive Multifunctional Photoelectric Device Based on Discotic Columnar Nanostructures and Molecular Motors. Issue 8 (7th January 2019) - Zou, Cheng; Sun, Jian; Wang, Meng; Wang, Jingxia; Wu, Yuchen; Zhang, Lanying; Zhu, Zhongpeng; Xiong, Guirong; Jiang, Lei; Ikeda, Tomiki; Yang, Huai
Abstract: Orientation control of ordered materials would not only produce new physical phenomenon but also facilitate the development of fancy devices. Discotic liquid crystals (DLCs) form 1D charge transport pathway by self‐organizing into columnar nanostructures via π–π stacking. However, controlling the electrical properties in such nanostructures with some direct and instant way is a formidable task for their high viscosity and insensitivity to external stimuli. Herein, the arbitrary control over electrical conductivity of such columnar nanostructures is achieved with UV light by incorporating DLCs with molecular motors. Highly ordered DLC microstripe arrays are generated on desired substrate through a capillary bridge dewetting strategy. The conductivity of the microstripes could be continuously modulated by 365 nm light due to the influence of molecular motion under UV irradiation on the electron orbital overlap of columnar nanostructures. This is so because the disorder degree of the DLC molecules is associated with the intensity of UV light and the doping concentration of molecular motors. Moreover, the device shows memory effect and reversible conductivity change. The DLC microstripe arrays are very promising for the applications in UV detectors, memory devices, optical switches, and so on. Abstract : Discotic columnar nanostructures with uniform alignment are prepared on a Si/SiO2 substrate through a capillary dewetting strategy. The conductivity of the microstripes could be continuously modulated by 365 nm UV light. The device shows memory effects and thermorecovery, which is promising for application of multifunctional integrated devices.